Komunis di Dalam Negeri, Kapitalis di Luar Negeri Investasi RRT dan Implikasinya Terhadap Indonesia - Rosdiansyah Rosdiansyah (Jurnal Mengkaji Indonesia, 2022)
Abstract: This article examines the various investments made by Tiongkok in a number of countries, one of which is Indonesia in an effort to expand its economic hegemony in the international world. The Beijing consensus is the foundation of the People's Republic of Tiongkok in strengthening its economic position by providing foreign investment to developing countries, both in Asia and Africa. Although adopting communism as the principle of domestic politics, the pattern of expansion of investment carried out by Tiongkok under Xi Jinping actually leads to capitalism and neoliberalism as stated in the points contained in the Beijing Consensus. Purpose: This article seeks to explore the process of Tiongkok investment abroad. Design/Methodology/Approach: This article uses a literature review as the research method. Findings: This article finds that despite using the ideology of communism for its domestic hegemony, Tiongkok applies a capitalist economic style in its foreign investment and foreign trade. Originality/Value: The novelty of this article is the author's attempt to explain the differences between Tiongkok's trading style and the logic of its domestic power.